Analysis of Monoclonal Antibodies by Capillary Electrophoresis: Sample Preparation, Separation, and Detection - Meriem Dadouch; Yoann Ladner; Catherine Perrin (Separations, 2021)
Therapeutic monoclonal antibodies (mAbs) are dominating the biopharmaceutical field due to the fact of their high specificity in the treatment of diverse diseases. Nevertheless, mAbs are very complex glycoproteins exhibiting several macro- and microheterogeneities that may affect their safety, quality, and efficacy. This complexity is very challenging for mAbs development, formulation, and quality control. To tackle the quality issue, a combination of multiple analytical approaches is necessary. In this perspective, capillary electrophoresis has gained considerable interest over the last decade due to the fact of its complementary features to chromatographic approaches. This review provides an overview of the strategies of mAbs and derivatives analysis by capillary electrophoresis hyphenated to ultraviolet, fluorescence, and mass spectrometry detection. The main sample preparation approaches used for mAb analytical characterization (i.e., intact, middle-up/down, and bottom-up) are detailed. The different electrophoretic modes used as well as integrated analysis approaches (sample preparation and separation) are critically discussed.